Physician professional motivation and online knowledge sharing for patient education: a perspective of motivation theory - Yun Huang; Junping Guo; Yan Wen; Qihui Fan (Frontiers in Public Health)
AimsDrawing on motivation theory, this study aims to investigate the effect of professional motivation on online knowledge sharing for patient education with considering the contingencies of online experience and offline expertise.MethodsBased on a panel dataset comprising 11,839 physicians with 24,389 physician-month observations selected from one of leading online health platforms in China, this study conducted the fixed hierarchical regression model to test the direct and moderating effects.ResultsThe results show that professional motivation positively affects online knowledge-sharing quantity and quality. Meanwhile, online experience enhances the positive effects of professional motivation on the above two dimensions of online knowledge sharing. In addition, offline expertise hinders the benefits of professional motivation to online knowledge-sharing quantity.ConclusionThis study makes contributions to the literatures of motivation theory, online knowledge sharing, online and offline contexts on online health platforms, and provides implications for physicians and platform managers.